Systematic revision and phylogeny of Paragripopteryx Enderlein, 1909 (Plecoptera: Gripopterygidae) - Duarte, Tácio; Calor, Adolfo Ricardo; da Conceição Bispo, Pitágoras [UNESP] (Public Library of Science (PLoS), 2022)
Among the Neotropical gripopterygids, the genus Paragripopteryx occurs along the Brazilian Atlantic coast to Uruguay. Since its first recognition by Enderlein in 1909, the genus underwent a confusing taxonomic history with some combinations. In this study, we aim to revise Paragripopteryx and present the first morphology-based phylogeny for the genus. The analysis comprised 38 morphological characters and their respective states in 30 terminal taxa, including 13 Paragripopteryx species, two new species identified as belonging to Paragripopteryx, and 15 outgroup species, among which we can highlight 12 different South American genera and one Australian genus of Gripopterygidae. The cladistic analysis yielded a parsimonious tree for k = 3 (137 steps, consistency index = 0.445, and retention index = 0.591) where most Paragripopteryx are nested, except for Uruguayan Paragripopteryx munoai. We can then infer that in its current circumscription Paragripopteryx is polyphyletic. The following two species are described: Paragripopteryx dasalmas sp. nov. and Paragripopteryx ogum sp. nov. Paragripopteryx baratinii is designated as a nomen dubium. Additionally, we provide a key for species identification, updated geographical records, and illustrations for all species. As a corollary, our study gathers relevant morphological information that can help to better understand this genus and create foundations for the next steps.